2018
DOI: 10.7717/peerj.4424
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco rattle virus-inducedPHYTOENE DESATURASE(PDS)andMg-chelatase H subunit(ChlH) gene silencing inSolanum pseudocapsicumL.

Abstract: Virus-induced gene silencing (VIGS) is an attractive tool for determining gene function in plants. The present study constitutes the first application of VIGS in S. pseudocapsicum, which has great ornamental and pharmaceutical value, using tobacco rattle virus (TRV) vectors. Two marker genes, PHYTOENE DESATURASE (PDS) and Mg-chelatase H subunit (ChlH), were used to test the VIGS system in S. pseudocapsicum. The photobleaching and yellow-leaf phenotypes of the silenced plants were shown to significantly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
4
12
1
Order By: Relevance
“…From the 20 inoculated plants with the pTRV2:PpPDS vector, 10 plants showed photo-bleaching leaves indicating a rate efficiency of 50 %, which is consistent with other reports [40,42,43] (Fig. 4).…”
Section: Gene Silencing Experimentssupporting
confidence: 90%
“…From the 20 inoculated plants with the pTRV2:PpPDS vector, 10 plants showed photo-bleaching leaves indicating a rate efficiency of 50 %, which is consistent with other reports [40,42,43] (Fig. 4).…”
Section: Gene Silencing Experimentssupporting
confidence: 90%
“…According to our results, it did not affect our judgment to silencing phenotype. We found that described above silencing spots also appeared in other VIGS experiments, S. pseudocapsicum, cotton and pepper sliencing by TRV, N. benthamiana sliencing by CaLCuV, and so on [22,[35][36]65].…”
Section: Discussionsupporting
confidence: 61%
“…Tuttle et al discovered that the ambient temperature needed to be lower than 21 °C to obtain a better silencing phenotype and that TRV-mediated VIGS was almost completely inhibited when the ambient temperature was higher than 28 °C [35]. Xu et al (2018) tested silencing efficiency by TRV under different growth temperatures (18 °C, 25 °C and 30 °C), and the speed of the response and the efficiency of infection were optimal at 25 °C [36]. In our study, the 22 °C is the most suitable temperature for PCVA/PVCB in cabbage, suggesting that appropriate low temperature can improve silence efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, HIGS has also proved to be a promising strategy for silencing a foreign gene in a host to investigate numerous plant-pathogen systems [61,62], including Vd in various hosts [33,34,63]. In the present study, positive plants at 10 days after infiltration showed distinct photobleaching, suggesting the massive presence of dsRNA and its active role in gene silencing [64][65][66]. In our study, seedlings that were inoculated with Vd developed varying degrees of wilting from 10 to 12 dpi.…”
Section: Discussionsupporting
confidence: 57%